The Need for Innovation of Security Education for Strengthening the Results of Traditional Teaching at Universities - Vackova, Martina; Kovacova, Lucia; Kancirova, Maria; Losonczi, Peter (Communications - Scientific letters of the University of Zilina, 2016)
This article deals with security education and the possibilities of innovative methods application in this kind of education at universities. The continuous development of science and technology, as well as constantly changing social needs which are closely tied to the emergence of new security risks and threats, dynamically affect the entire system of education. Therefore, an urgent need for the implementation of these requirements arises. There is a need to address the number of key roles in the framework of security education in the spirit of innovation methods in order to improve teaching and, subsequently increase the efficiency of the process.